Geophagic termite mounds as one of the resources for African elephants in Ugalla Game Reserve, Western Tanzania. (11th July 2016) - Kalumanga, Elikana; Mpanduji, Donald G.; Cousins, Sara A. O.
Abstract: Knowledge of the distribution and nutrient values of key resources supporting the survival of wildlife species is integral for an effective conservation planning and management of the species. In the Miombo ecosystem of the Ugalla Game Reserve, African elephants ( Loxodonta africana Blumenbach 1797), eat soil, that is geophagy, from certain termite mounds. We mapped that all the geophagic termite mounds are exclusively situated in the flood plain. To understand why soils from some termite mounds are eaten, we collected and analysed soil samples from 10 geophagic termite mounds, seven nongeophagic termite mounds and 13 samples from the surrounding flood plain. Percentage of clay content did not differ significantly among the soil samples. Soils from geophagic termite mounds were richer in mineral elements compared with other soil samples. The results demonstrate that the driver for geophagic behaviour is related to rich mineral element contents found in geophagic termite mounds made of the mineral‐enriching termites (Macrotermes). Thus, geophagic termite mounds play a role in elephant's dietary needs and possibly influence their movement patterns in Ugalla, as the elephants cannot obtain enough minerals from their feeds. Geophagic termite mounds should be protected from potential destructive land uses, such as airstrip construction.